Kirkelig organisering og ledelse Et verdibasert og praksisorientert perspektiv - Sirris, Stephen; Askeland, Harald (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
" What is unique about leadership and leadership roles in the Church of Norway? In what ways does the Church's organization reflect its mission? These are among the questions raised by the transition from state church to independent national church, internal reforms, and development of a new organizational structure. The objective of this anthology is to provide new insight into organization and management of a church in transition. The articles analyse various aspects of development such as democratization, professionalization, and bolstering the Church's administrative organization. Empirical investigation of the church begins in studies of organization and leadership, enabling a dialogue between what is unique in the context of the Church and general organizational theory. The book sheds light on the church's distinctive empirical ecclesiological and organization-theoretical features. The authors adopt a values-based and practice-oriented perspective, taking into account the Church's identity and values as both a religious community and an organization with a wide range of activities and leadership practices on display. Church Organization and Management is aimed primarily toward students in educational programs qualifying them for church service as well as church employees, managers, and advisory board members. This book will also provide researchers in organization and management with an introduction to the field of the church and its context. This book is the result of an initiative by the section for values-based leadership at VID Specialized University, and its authors have drawn on lengthy teaching and research experience on the Church of Norway. The book's editors are Stephen Sirris, associate professor at VID's Faculty of Theology, Diaconia and Leadership Studies, and Harald Askeland, professor at VID's Faculty of Theology, Diaconia and Leadership Studies."